Hubungan antara Dukungan Sosial Keluarga dengan Kepatuhan Minum Obat Penderita Kusta (Studi di Kecamatan Puger dan Balung Kabupaten Jember) The Relationship between Family Social Support with Medicine Compliance of Leprosy Patients (Study in Kecamatan Bal - Yusi Prelian Saputri; Thohirun Thohirun; Novia Luthviatin (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Abstract Leprosy (Morbus hansen) is a chronic disease caused by Mycobacterium leprae that attacks the peripheral nerve, skin, mouth, upper respiratory tract, endothelial reticulocyte system, eyes, muscles, bones and testes. Many factors that can influence the compliance of taking medication in leprosy patients, one of them is family social support. The aim of this research was to analyzing the relationship between family social support with medicine compliance of leprosy patients. The research method used was observasional analytic with cross sectional design. The sample 53 respondents were a total sampling. The result of the bivariate analysis that respondents who had good emotional support and good medicine compliance were 37 respondents (69.8%). Respondents who had good assessment support and good medicine compliance were 36 respondents (67.9%). Respondents who have good information support and good medicine compliance were to 33 respondents (62.3%). Respondents who have good instrumental support and good medicine compliance were 36 respondents (67.9%). Based on this research results can be concluded that there is a relationship between emotional support, assessment support, information support and instrumental support with medication compliance of leprosy patients. Keywords: Leprosy, Family Social Support, Drugs Compliance